Law of armed conflict : international humanitarian law in war - "Solis, Gary D" (New York, 2016)
Newly revised and expanded, The Law of Armed Conflict, 2nd edition introduces law students and undergraduates to the law of war in an age of terrorism. What law of armed conflict (LOAC), or its civilian counterpart, international humanitarian law (IHL), applies in a particular armed conflict? Are terrorists legally bound by that law? What constitutes a war crime? What (or who) is a lawful target and how are targeting decisions made? What are 'rules of engagement' and who formulates them? How can an autonomous weapon system be bound by the law of armed conflict? Why were the Guantánamo military commissions a failure? This book takes students through these LOACIHL questions and more, employing real-world examples and legal opinions from the US and abroad. From Nuremberg to 9/11, from courts-martial to the US Supreme Court, from the nineteenth century to the twenty-first, the law of war is explained, interpreted, and applied.
Keywords: Law